2016
DOI: 10.3168/jds.2016-11422
|View full text |Cite
|
Sign up to set email alerts
|

Separation of milk fat globules via microfiltration: Effect of diafiltration media and opportunities for stream valorization

Abstract: Milk fat globule membranes (MFGM) sourced in buttermilk have gained recent interest given their nutritional value and functional properties. However, production of isolated MFGM has been challenging given their size similarity with casein micelles, which limits attempts toward fractionation by size exclusion techniques. Therefore, the hypothesis underpinning this study is that the removal of proteins from cream before butter-making facilitates MFGM isolation. As such, milk fat globules were separated from raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The results for zeta potential coincided with those of particle size, indicating that the given processing modified the surface of the milk fat globules and possibly released MFGM components due to shear stress and change in the equilibria. A more negative zeta potential of milk fat globule upon microfiltration was reported previously by Jukkola et al, [23] and was explained by a decrease in mineral composition. Furthermore, Bourlieu et al [42] reported an accumulation of free fatty acids on the MFGM that made the zeta potential more negative (and increased the electrostatic repulsion).…”
Section: Particle Size and Zeta Potentialsupporting
confidence: 76%
See 4 more Smart Citations
“…The results for zeta potential coincided with those of particle size, indicating that the given processing modified the surface of the milk fat globules and possibly released MFGM components due to shear stress and change in the equilibria. A more negative zeta potential of milk fat globule upon microfiltration was reported previously by Jukkola et al, [23] and was explained by a decrease in mineral composition. Furthermore, Bourlieu et al [42] reported an accumulation of free fatty acids on the MFGM that made the zeta potential more negative (and increased the electrostatic repulsion).…”
Section: Particle Size and Zeta Potentialsupporting
confidence: 76%
“…The shear-induced damage was estimated based on particle size and zeta potential measurements. The particle size was expected to increase due to permeation of the smallest fat globules and casein micelles [23]. However, microfiltration decreased the mean fat globule size slightly after the first cycle (Table 1) after which the particle size remained constant.…”
Section: Particle Size and Zeta Potentialmentioning
confidence: 99%
See 3 more Smart Citations